HUBUNGAN PERILAKU IBU TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT TERHADAP STATUS KARIES GIGI ANAK Tinjauan Berdasarkan Pengetahuan, Tingkat Pendidikan, dan Status Sosial di TK ABA 1 Banjarmasin Kajian di Puskesmas Kota Banjarmasin Bulan September-Oktober 2014 - Afiati, Risti; Adhani, Rosihan; Ramadhani, Karina; Diana, Sherli (FKG Unlam, 2017)
ABSTRACTBackground: Oral health disease places the first rank among the most ten diseases in Indonesia. The main oral health problem of children is dental caries. Mother is the closest figure of pre-school children who becomes a role model for her children. The purpose of this research determined the correlation between knowledge, education, and social status of mothers and the dental caries status of students in TK ABA 1 Banjarmasin. Methods: This research used analytical survey method with cross sectional approach. There were 46 samples selected in this research by using purposive sampling method based on certain inclusion criteria. Instrument used in this research was questionnaire to measure mothersâ knowledge, education level, and social status. Studentsâ dental caries status was measured base on def-t index. Result: In this research, the researcher correlated the knowledge, education level, social status of the mothers and the studentsâ dental caries status index by using SPSS and Spearman test. The result revealed the correlation is negative. It shows the higher knowledge, education level, and social status of the mother, the lower were def-t index of the students. The correlational strength was < 0.8 (strong) and p value was < 0.05 which means significant correlation. Conclusion: There is a significant correlation between knowledge, education level, social status of mothers and the studentsâ dental caries status.Keywords: Mother knowledge, mother education level, mother economy status, kindergarten students